Antifungal mechanism of volatile compounds emitted by Actinomycetota Paenarthrobacter ureafaciens from a disease-suppressive soil on Saccharomyces cerevisiae - Tri-Phuong Nguyen; De-Rui Meng; Ching-Han Chang; Pei-Yu Su; Chieh-An Ou; Ping-Fu Hou; Huang-Mo Sung; Chang-Hung Chou; Masaru Ohme-Takagi; Hao-Jen Huang (mSphere, 2023)
ABSTRACT Increasing evidence suggests that in disease-suppressive soils, microbial volatile compounds (mVCs) released from bacteria may inhibit the growth of plant-pathogenic fungi. However, the antifungal activities and molecular responses of fungi to different mVCs remain largely undescribed. In this study, we first evaluated the responses of pathogenic fungi to treatment with mVCs from Paenarthrobacter ureafaciens. Then, we utilized the well-characterized fungal model organism Saccharomyces cerevisiae to study the potential mechanistic effects of the mVCs. Our data showed that exposure to P. ureafaciens mVCs leads to reduced growth of several pathogenic fungi, and in yeast cells, mVC exposure prompts the accumulation of reactive oxygen species. Further experiments with S. cerevisiae deletion mutants indicated that Slt2/Mpk1 and Hog1 MAPKs play major roles in the yeast response to P. ureafaciens mVCs. Transcriptomic analysis revealed that exposure to mVCs was associated with 1,030 differentially expressed genes (DEGs) in yeast. According to gene ontology and Kyoto Encyclopedia of Genes and Genomes analyses, many of these DEGs are involved in mitochondrial dysfunction, cell integrity, mitophagy, cellular metabolism, and iron uptake. Genes encoding antimicrobial proteins were also significantly altered in the yeast after exposure to mVCs. These findings suggest that oxidative damage and mitochondrial dysfunction are major contributors to the fungal toxicity of mVCs. Furthermore, our data showed that cell wall, antioxidant, and antimicrobial defenses are induced in yeast exposed to mVCs. Thus, our findings expand upon previous research by delineating the transcriptional responses of the fungal model. IMPORTANCE Since the use of bacteria-emitted volatile compounds in phytopathogen control is of considerable interest, it is important to understand the molecular mechanisms by which fungi may adapt to microbial volatile compounds (mVCs). Paenarthrobacter ureafaciens is an isolated bacterium from disease-suppressive soil that belongs to the Actinomycetota phylum. P. ureafaciens mVCs showed a potent antifungal effect on phytopathogens, which may contribute to disease suppression in soil. However, our knowledge about the antifungal mechanism of mVCs is limited. This study has proven that mVCs are toxic to fungi due to oxidative stress and mitochondrial dysfunction. To deal with mVC toxicity, antioxidants and physical defenses are required. Furthermore, iron uptake and CAP proteins are required for antimicrobial defense, which is necessary for fungi to deal with the thread from mVCs. This study provides essential foundational knowledge regarding the molecular responses of fungi to inhibitory mVCs.